Subcutaneous Fat Necrosis of the Newborn: A Case Report (Journal of Bangladesh College of Physicians and Surgeons, 2017)
We report a case of Subcutaneous Fat Necrosis (SCFN) of a newborn which is an uncommon disorder, occurs during the first year of life, and has been attributed to perinatal stress. SCFN usually has a favorable prognosis, with complete autoresolution of subcutaneous lesions within several weeks or months, but it may also be complicated by serious metabolic alterations such as hypercalcemia.J Bangladesh Coll Phys Surg 2017; 35(4): 192-195